Preparation and In-Vitro Evaluation as an Oral Microsponge Tablet of Baclofen - Alatraqchi, Faten Ibraheem; J. AL Gawhri, Fatima (Iraqi Journal of Pharmaceutical Sciences, 2019)
The aim of the present study is to formulate floating effervescent microsponge tablet of the narrow absorption window drug, Baclofen (BFN) for controlling drug release and thereby decrease the side effect of the drug. The microsponges of BFN were prepared by non-aqueous emulsion solvent diffusion method (oil in oil emulsion method). The effects of drug: polymer ratio, stirring time and type of Eudragit polymer on the physical characteristics of microsponges were investigated and characterized for production yield, loading efficiency, particle size, surface morphology, and in vitro drug release from microsponges. The selected microsponge formula was incorporated into the floating effervescent gastro-retentive tablet. The prepared floating microsponge tablet was evaluated for tablet hardness, friability, swelling in addition to in vitro drug release. The results showed that the microsponge formula with Eudragit RS100 had optimum physical properties and controlled drug release (75% of drug release in 8 hr.) when compared with other formulas and pure baclofen. The oil in oil emulsion method is a promising method to produce baclofen microsponge.